PENGARUH FASILITAS KERJA, LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP SEMANGAT KERJA GURU PADA MTs AL-HUDA PEKANBARU - Putra, Eka (Eko dan Bisnis: Riau Economic and Business Review, 2018)
Every good institution engaged in education or other fields, certainly has a vision and mission. In fact, there are some things that still not optimally performed by teacher educators who are at MTs Al-Huda Pekanbaru, of which there are many teachers who have not completed their teaching device that should be the beginning of the semester learning devices These must already exist. And also still often found empty classes because teachers have still not even come that late hour lesson when effective progress. Population and sample in this research are as many as 47 teachers at MTs Al-Huda Pekanbaru, this study was conducted in December 2016, which is located at Jalan HR Soebrantas Pekanbaru. To answer the formulation, objectives and hypotheses of the study then used the Statistical Package for the Social Sciences (SPSS). The results of the study that in partial Influence of working facilities to teachers working seangat (sig < 0,05), meaning that partially positive and significant impact includes work on morale of teachers, thus Ho is rejected and Ha accepted. Working environmental influences on morale of teachers (sig < 0,05), meaning that partially there is a positive influence and significant correlation between the work environment to the morale of teachers, thus Ho is rejected and Ha accepted. That is, the better the work environment, the higher the morale of teachers, conversely the lower the quality of the work environment, the lower the morale of teachers. The influence of organizational culture on teachers 'morale (sig < 0,05), meaning that partially positive and significant effect between organizational culture on teachers' morale, thus Ho is rejected and Ha accepted".